2017
DOI: 10.1111/birt.12280
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of vaginal breech birth training strategies: An integrative review of the literature

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Simulation training in vaginal birth management is therefore important. Nonetheless, no conclusive practice recommendations are available, owing to the heterogeneity of studies 20 . Australia 21 and England 15 recommend annual drills for obstetrics skills including vaginal birth management.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation training in vaginal birth management is therefore important. Nonetheless, no conclusive practice recommendations are available, owing to the heterogeneity of studies 20 . Australia 21 and England 15 recommend annual drills for obstetrics skills including vaginal birth management.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review suggested that experienced mentorship in clinical practice is an important corollary to breech training, associated with higher rates of attendance at actual vaginal breech births . Models of specialist care provision have been explored with good results in areas such as twin pregnancy and birth and birth after cesarean delivery .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review suggested that experienced mentorship in clinical practice is an important corollary to breech training, associated with higher rates of attendance at actual vaginal breech births. 18 Models of specialist care provision have been explored with good results in areas such as twin pregnancy and birth 19 and birth after cesarean delivery. 20,21 While much work has been done on the benefits of models of continuity of caregiver provided by midwives, 22,23 less research has addressed the impact of continuity of obstetric caregiver, and trusting, stable relationships within the professional team.…”
Section: Discussionmentioning
confidence: 99%
“…
Citation: Walker, S., Scamell, M. and Parker, P. M. (2017). Deliberate acquisition of competence in physiological breech birth: A grounded theory study.
…”
mentioning
confidence: 99%